Economies of Abandonment : Social Belonging and Endurance in Late Liberalism - Povinelli, Elizabeth A. (Book collections on Project MUSE., 2011)
"In Economies of Abandonment, Elizabeth A. Povinelli explores how late liberal imaginaries of tense, eventfulness, and ethical substance make the global distribution of life and death, hope and harm, and endurance and exhaustion not merely sensible but also just. She presents new ways of conceptualizing formations of power in late liberalis - the shape that liberal governmentality has taken as it has responded to a series of legitimacy crises in the wake of anticolonial and new social movements and, more recently, the "clash of civilizations" after September 11. Based on longstanding ethnographic work in Australia and the United States, as well as critical readings of legal, academic, and activist texts, Povinelli examines how alternative social worlds and projects generate new possibilities of life in the context of ordinary and extraordinary acts of neglect and surveillance. She focuses particularly on social projects that have not yet achieved a concrete existence but persist at the threshold of possible existence. By addressing the question of the endurance, let alone the survival, of alternative forms of life, Povinelli opens new ethical and political questions"--Back cover